PERENCANAAN MESIN PEMIPIL JAGUNG TENAGA SEPEDA MOTOR BEBEK (UNDERBONE) HONDA SUPRA X 125R DENGAN KAPASITAS 500 KG/JAM - Sugeng Hariyadi; Dedy Rachmad Ardian; Hisbulloh Ibrohim (Wahana Teknik, 2022)
This research was conducted to make a more effective and efficient equipment to facilitate the processing of corn with a corn sheller machine. This corn sheller machine will later be intended for independent farmers who shell corn in the direct rice field area, which previously had dried the corn on their plants so that a sheller machine was needed that could peel the corn and its husks. Besides that, these farmers usually use motorcycles, especially the Honda Supra X 125R underbone motorcycle which is often found as a mobility vehicle to the rice field area, therefore researchers are looking for more benefits from the farmers' motorcycle vehicles which are intended for mobility only, but now they can It is also used as a driving force for the corn sheller machine so that when the corn is harvested it can be peeled directly using a corn sheller engine powered by a Honda Supra X 125R motorcycle. Then for the corn sheller machine itself, it uses a model of the corn sheller machine with the rice thresher method (direct feeder type) with a capacity of 500 kg/hour so that when farmers go home from the fields, they can directly bring clean corn shells.